West Nile virus in vultures from europe – a sight among other raptors - Loureiro, Filipa (Slovenian veterinary research, 2024)
The West Nile virus (WNV) is an arbovirus mainly transmitted by Culex spp. and the causative agent of a zoonotic disease that is present worldwide. This pathogen is endemically maintained in a life cycle with birds acting as reservoirs, and humans and horses as accidental and dead-end hosts. Sporadic WNV outbreaks have been reported in Europe, and the potential impact of WNV infection on populations of threatened or endangered birds of prey is considerable. Surveillance programs are needed for early detection of this virus. All four species of vultures present in Europe are considered protected species. As scavengers, vultures are at the top of the food chain, and can be susceptible to, and negatively affected by, pathogens like WNV. In a conservation perspective, the impact of WNV in European vultures, alone or concomitantly with other factors, should be addressed. This review of documented cases can be considered a starting point.
Keywords: epidemiology; Europe; scavengers; vultures; West Nile virus; zoonotic